Anoikis Resistance as a Further Trait of Acidic-Adapted Melanoma Cells. (2nd June 2019) - Peppicelli, Silvia; Ruzzolini, Jessica; Bianchini, Francesca; Andreucci, Elena; Nediani, Chiara; Laurenzana, Anna; Margheri, Francesca; Fibbi, Gabriella; Calorini, Lido
Abstract : Melanoma is characterized by a low extracellular pH, which contributes to the development of an aggressive phenotype characterized by several properties as the switch to an epithelial-to-mesenchymal program, the increase of apoptotic resistance, and the migratory ability together with the development of drug resistance. Here, we demonstrate that melanoma cells grown in low pH medium (pH 6.7) for a short (24 hours) or long (at least 3 months) period equally express an anoikis resistance profile. Anoikis is a form of apoptosis prompted by loss of adhesion, particularly requested by aggressive cancer cells to metastasize. Anoikis resistance was ascertained in acidic melanoma cells either grown in agarose-coated plates or incubated in rocking conditions. Both analyses indicate that acidic cells were more able to survive in a nonadherent condition than cells grown in standard pH, an effect resulting in a more cloning efficiency and migratory ability. Ability to survive during rocking was inhibited using mTOR/NF-kB inhibitors. Finally, we checked whether characteristics related to the in vitro anoikis resistance acquired by acidic melanoma cells might be also suitable for in vivo challenge. We injected acidic melanoma cells into blood stream, and then we verify how many cells survived in blood after 15 min from the injection. Only acidic cells, transient and chronic, survived, whereas melanoma cells grown in standard pH medium did not. Overall, we have had the opportunity to demonstrate that low extracellular pH represents an additional mechanism able to promote an anoikis resistance in solid tumors.